Analysis Mixed Layer Asphalt Surface as Asbuton Ac-Wc Characteristics of Marshall - Huda Alfian Aunur Hasyir; Sapto Budi Wasono (LPPM NAROTAMA UNIVERSITY, Indonesia, 2020)
Natural asphalt is asphalt obtained somewhere in nature, and can be used as obtained or with little processing. No natural asphalt obtained in the mountains like asphalt in Buton island called Asbuton. Asphalt Buton island is a mixture of bitumen material with other mineral materials in the form of rocks. Because asbuton is so sajaa material found in nature, the levels of bitumen dikandungnyaa greatly varies from low to high. To overcome this, then asbuton began to be produced in various forms at the processing plant asbuton. To reduce the use of natural asphalt eat more steps to do research on utilizing asbuton with the composition 6%, 8%, 10%. The purpose of this study is 1.) Determine the material characteristics LGA Asbuton can meet the specifications of Highways in 2018 on a mix of AC-WC 2.) Determine the value of Optimum Asphalt Content on asphalt concrete AC-WC (Asphalt Concrete - Wearing Course) with extra material LGA Asbuton 3.) Knowing how the performance of asphalt concrete AC-WC with additional material and bitumen 60/70 Asbuton terms of Marshall Test. The study was conducted with an experimental method through laboratory testing. The expected benefits of this research is the discovery of optimizing the use of Asbuton for at the time of execution of the work of new road construction or road maintenance and provide alternative natural aggregate material consumption to a minimum.The test results for the optimum bitumen content KAO on the composition 1 Asbuton 6% with a variation of bitumen (5.05% 5.55% 6.05% 6.55% 7.05%) of the chart can be found KAO Marshall 6.2%. Composition 2 Asbuton 8% with a variation of asphalt (5.0% 5.5% 6.0% 6.5% 7.0%) on the graph can be found KAO Marshall 6.3%. Composition 3 Asbuton 10% with a variation of asphalt (5.0% 5.5% 6.0% 6.5% 7.0%) on the graph can be found KAO Marshall 6.4%. Variations in the composition of 6%, 8% and 10% meet all the requirements of the properties of hot asphalt mix can specification of Highways in 2018.